2021
DOI: 10.35848/1347-4065/ac1644
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of interfacial effects on low-energy electron dynamics in chemically amplified resist processes of photomask fabrication

Abstract: The resist thickness has decreased with the miniaturization of transistors. In chemically amplified electron beam resists used for photomask fabrication, thermalized electrons play an important role in acid generation. The interfacial effects of low-energy electrons strongly affect the latent image formation in thin resist films. In this study, we investigated the relationships between the boundary conditions of low-energy electrons at interfaces and the protected unit distribution in terms of resist thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For the chemically amplified EB resists, such lowenergy electron dynamics at the resist-substrate interface were experimentally confirmed to affect the resist pattern shapes. 27) Note that the low-energy secondary electrons mentioned here 28,29) are different from the well-known backscattered electrons in EB lithography. 30,31) The backscattered electrons generally do not get involved in the interfacial effect, because they go through the ultrathin films.…”
Section: Introductionmentioning
confidence: 86%
“…For the chemically amplified EB resists, such lowenergy electron dynamics at the resist-substrate interface were experimentally confirmed to affect the resist pattern shapes. 27) Note that the low-energy secondary electrons mentioned here 28,29) are different from the well-known backscattered electrons in EB lithography. 30,31) The backscattered electrons generally do not get involved in the interfacial effect, because they go through the ultrathin films.…”
Section: Introductionmentioning
confidence: 86%
“…Thus far, many modeling and simulations of sensitization that occur in CARs have been performed. [45][46][47][48] In addition, recently, machine-learning-based data analysis of the simulation has been conducted. [49][50][51][52] Furthermore, molecular orientation and resist reaction analysis using MD calculation is being vigorously pursued in the prediction of the resist physics and chemistry.…”
Section: Calculations Of Car With the Agpmentioning
confidence: 99%
“…[10][11][12][13][14] The interface effects on resist pattern formation are among the problems related to resist thickness. [15][16][17][18][19][20][21][22][23][24][25][26][27] It has been reported that the interaction between polymers and substrates affects the glass transition temperature of polymer films. [20][21][22][23] The interface between resists and underlayers has also been reported to affect lowenergy (less than the electronic excitation energy of organic materials) electrons and the subsequent acid generation in chemically amplified resists.…”
Section: Introductionmentioning
confidence: 99%